2002
DOI: 10.1111/j.1752-1688.2002.tb04357.x
|View full text |Cite
|
Sign up to set email alerts
|

CLIMATIC AND HYDROLOGIC VARIABILITY IN A COASTAL WATERSHED OF SOUTHWESTERN BRITISH COLUMBIA1

Abstract: Climate data from the Malcolm Knapp Research Forest (MKRF) in the Coast Range mountains of southwestern British Columbia were used to examine relationships between climate and hydrology and variations in the El Niño Southern Oscillation (ENSO) and Pacific Decadal Oscillation (PDO). Air and water temperatures were higher and precipitation was lower during in‐phase or warm PDO/E1 Niño events than in other years. In contrast, in‐phase or cool PDO/La Niña years were generally cooler and wetter than other years. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 37 publications
3
62
1
Order By: Relevance
“…Hartmann and Wendler (2005) also indicated the importance of accounting for such changes in analyses of long-term climate variations and change. Kiffney et al (2002) assessed long-term climate variability in a south coastal BC watershed. They found that air temperature was higher during warm PDO/El Niño, and cooler during cool PDO/La Niña.…”
Section: Temperaturementioning
confidence: 99%
“…Hartmann and Wendler (2005) also indicated the importance of accounting for such changes in analyses of long-term climate variations and change. Kiffney et al (2002) assessed long-term climate variability in a south coastal BC watershed. They found that air temperature was higher during warm PDO/El Niño, and cooler during cool PDO/La Niña.…”
Section: Temperaturementioning
confidence: 99%
“…One of the most established modulations is that of PDO on ENSO, which results in El Niño (La Niña) being strong and stable when PDO is positive (negative) (Kiffney et al, 2002;Whitfield et al, 2010;Gershunov and Barnett, 1998). During these occasions, PDO and ENSO are said to be in-phase, or constructive (Kiffney et al, 2002).…”
Section: Enso Is Characterized By Fluctuating Sea Surface Temperaturementioning
confidence: 99%
“…PDO and ENSO are said to be out-of-phase, or destructive, during the inverse phases (Kiffney et al, 2002). Constructive phases produce a strong, coherent precipitation response and destructive phases produce a weakened, spatially incoherent response (Gershunov and Barnett, 1998).…”
Section: Enso Is Characterized By Fluctuating Sea Surface Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…We report on study results for the first 6 years involving instream physical habitat and fish size and abundance, and we summarize specific aspects of stream temperature and discharge. Detailed results for instream chemical, water volume, and thermal variables; climate; and measures of nonfish aquatic biota (primary production, invertebrates) and terrestrial biota (insects, amphibians, mammals) are in preparation or reported elsewhere (e.g., Kiffney et al 2000Kiffney et al , 2002Kiffney et al , 2003Cockle and Richardson 2003;.…”
mentioning
confidence: 99%